Characteristic plantar pressur distribution patterns during soccer-specific movements - Eils, P.; Streyl, M.; Linnenbecker, S.; Thorwesten, L.; Völker, K.; Rosenbaum, D. (The American Journal of Sports Medicine, 2004)
PURPOSE: To characterize in-shoe pressure measurements during different soccer-specific maneuvers on two playing surfaces to identify the main loading areas of the foot. METHODS: Twenty-one experienced male soccer players participated in the study (25.5 +/- 1.8 years, 78.7 +/- 5.4 kg, and 182.9 +/- 5.7 cm). The Pedar Mobile system was used to collect plantar pressure information inside the soccer shoe. Four soccer-specific movements were performed (normal run, cutting maneuver, sprint, and goal shot) on both a grass and a red cinder surface. RESULTS: Results showed characteristic pressure distribution patterns with specific loading areas of the foot that correspond to the evaluated movements. In addition, loading patterns with higher pressure values than those observed during normal run were found. In cutting, the medial part of the foot; in sprinting, the first and second ray; and in kicking, the lateral part of the foot are predominantly loaded. No global effect of the two surfaces on pressure parameters was found. CONCLUSION: The results of the present investigation suggest that the high load in soccer in combination with a high repetition may have an important influence in the development of overuse injuries.